Evaluation of a nonrandomized workplace health promotion program in a Spanish multinational company and its effects on cardiovascular risk factors and weight-related outcomes - Laura Gómez-Paredes; María José Aguado-Benedi; Luis Reinoso-Barbero (Archives of Community Medicine and Public Health - Peertechz Publications, 2022)
Objectives: The aim of this study was to evaluate the effects of a global health promotion intervention in the workplace on cardiovascular risk factors and weight-related outcomes in offices workers after two years.  Methods: This nonrandomized retrospective observational study analyzed data of two medical check-up of 728 office workers, over 40 years old: intervention group (376) and control (352) at baseline and after 2 years of a global health promotion program (based on nutrition, physical activity, and mental health) of mixed approach (individual, group and organizational) in the workplace of the intervention group.  Results: Systolic and diastolic blood pressure experienced a statistically significant decrease (p ˂ 0.05) at 2 years of -0.94 mm Hg and -0.79 mm Hg in the intervention group versus the control group whose changes were + 0.02 mm Hg and -0.38 mm Hg. Glucose also decreased 1.59 mg/dl more in the intervention group. Lipids, smoking, body mass index or waist circumference did not undergo relevant modifications.  Conclusion: This program improved blood pressure and glucose of office workers after two year follow-up, even among employees with low cardiovascular risk. However, according to the findings, this intervention was not as effective as expected in improving weight-related outcomes and cardiovascular risk in an office worker population.  Companies should strengthen, not only an overall health intervention, but also individual and personalized advice in the fight against cardiovascular risk.